Impacts of the creation, expansion and management of English wetlands on mosquito presence and abundance – developing strategies for future disease mitigation - Medlock, Jolyon M (Parasit Vectors, 2015)
The incidence of mosquito-borne diseases is increasing in Europe, partly due to the incursion of a number of invasive species known to be vectors of dengue and chikungunya viruses, but also due to the involvement of native species in the transmission of West Nile virus and malaria. For some of these pathogens, there is a risk of the re-emergence of vector-borne diseases that were once widespread in Europe, but declined partly due to large-scale land-drainage projects. Some mosquito species exploit container habitats as breeding sites in urban areas; an adaptation to human-made micro-habitats resulting from increased urbanisation. However, many species thrive in natural wetland ecosystems. Owing to the impacts of climate change there is an urgent need for environmental adaptation, such as the creation of new wetlands to mitigate coastal and inland flooding. In some cases, these initiatives can be coupled with environmental change strategies to protect a range of endangered flora and fauna species by enhancing and extending wetland landscapes, which may by driven by European legislation, particularly in urban areas. This paper reviews field studies conducted in England to assess the impact of newly created wetlands on mosquito colonisation in a) coastal, b) urban and c) arable reversion habitats. It also considers the impact of wetland management on mosquito populations and explores the implications of various water and vegetation management options on the range of British mosquito species. Understanding the impact of wetland creation and management strategies on mosquito prevalence and the potential risk of increasing the levels of nuisance or disease vector species will be crucial in informing health and well-being risk assessments, guiding targeted control, and anticipating the social effects of extreme weather and climate change. Although new wetlands will certainly extend aquatic habitats for mosquitoes, not all species will become a major nuisance or a vector concern as a result. Understanding how the design and management of wetlands might exacerbate mosquito densities is crucial if we are to manage nuisance mosquitoes and control vector species in the event of a disease outbreak. This entomological evidence-base will ensure that control strategies achieve optimal efficacy at minimal cost.